Lies that bind - Barbieri, Maggie (Barbieri, Maggie. Maeve Conlon novels., 2015)
"Maeve's moving on with everyday life when the unthinkable happens: her father dies of a massive heart attack. Maeve's mother died when Maeve was very young, and growing up, it was always just her and her father. But on the day of his funeral, Maeve learns a shocking secret: she might have a sister she's never met. Maeve knows her father would never have kept something like that from her--unless he thought he had to"--